Inhibiting autophagy to prevent drug resistance and improve anti-tumor therapy - Zamame Ramirez, Jofer Andree [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Kaneno, Ramon [UNESP] (Elsevier, 2021)
Cytotoxic drugs remain the first-line option for cancer therapy but the development of drug-resistance by tumor cells represents a primary obstacle for successful chemotherapy. Autophagy is a physiological mechanism of cell survival efficiently used by tumor cells to avoid cell death and to induce drug-resistance. It is a macromolecular process, in which cells degrade and recycle intracellular substrates and damaged organelles to alleviate cell stress caused by nutritional deprivation, hypoxia, irradiation, and cytotoxic agents, as well. There is evidence that autophagy prevents cancer during the early steps of carcinogenesis, but once transformed, these cells show enhanced autophagy capacity and use it to survive, grow, and facilitate metastasis. Current basic studies and clinical trials show the feasibility of using pharmacological or molecular blockage of autophagy to improve the anticancer therapy efficiency. In this review, we overviewed the pathways and molecular aspects of autophagy, its role in carcinogenesis, and the evidence for its role in cancer adaptation and drug-resistance. Finally, we reviewed the clinical findings on how the autophagy interference helps to improve conventional anticancer therapy.
Keywords: Autophagy; Cancer; Chemoresistance; Chemotherapy; Tumor escape